A phase I trial of the CDK 4/6 inhibitor palbociclib in pediatric patients with progressive brain tumors: A Pediatric Brain Tumor Consortium study (PBTC‐042). Issue 4 (6th January 2021) - Van Mater, David; Gururangan, Sridharan; Becher, Oren; Campagne, Olivia; Leary, Sarah; Phillips, Joanna J.; Huang, Jie; Lin, Tong; Poussaint, Tina Young; Goldman, Stewart; Baxter, Patricia; Dhall, Girish; et al.
Abstract: Background: Disruption of cell‐cycle regulators is a potential therapeutic target for brain tumors in children and adolescents. The aim of this study was to determine the maximum tolerated dose (MTD) and describe toxicities related to palbociclib, a selective cyclin‐dependent kinase 4/6 (CDK4/6) inhibitor in pediatric patients with progressive/refractory brain tumors with intact retinoblastoma protein. Methods: Palbociclib was administered orally starting at 50 mg/m 2 daily for the first 21 days of a 28‐day course. Dose escalation was according to the Rolling‐6 statistical design in less heavily (stratum I) and heavily pretreated (stratum II) patients, and MTD was determined separately for each group. Pharmacokinetic studies were performed during the first course, and pharmacodynamic studies were conducted to evaluate relationships between drug levels and toxicities. Results: A total of 21 patients were enrolled on stratum I and 14 patients on stratum II. The MTD for both strata was 75 mg/m 2 . Palbociclib absorption (mean T max between 4.9 and 6.6 h) and elimination (mean half‐life between 11.3 and 19.5 h) were assessed. The most common toxicity was myelosuppression. Higher palbociclib exposure was associated with grade 3/4 neutropenia and leukopenia. Dose limiting toxicities included grade 4 neutropenia and grade 3 thrombocytopenia and dehydration. No patients had an objective response to palbociclib therapy. Conclusions: Palbociclib was safely administered to children and adolescents at a dosage of 75 mg/m 2 for 21 consecutive days followed by seven days of rest in both strata. Future studies will establish its optimal utilization in pediatric patients with brain tumors.